Friendly visiting and partial enquiry (proof copy)
1902-02 1902 1900s 15 pages 11 II.— ST. GEORGE'S HOSPITAL. REPORTS BY MISS MUDD, Almoner, 1901. No. of patients seen by Almoner during 1901 4,378 Referred to Poor Law 11 Judged able to pay, and told fuller inquiry would be made on their return 278 Did not return to challenge inquiry, or dismissed themselves 185 Passed after inquiry 19 Refused treatment after inquiry 28 Patients referred to C.O.S. for further help, friendly visiting, or inquiry 160 Assisted 57 Convalesced 22 Open Air 3 Surgical Instruments 10 Other help 19 Not assisted 31 Friendly visits 28 Inquiries 24 Of the twenty-four cases sent for inquiry there were:— Patients' statements found to be true, and treatment granted 6 Found able to pay and dismissed 6 Wrong address given 5 Refused inquiry when visited by C.O.S. officers 3 Inquiries for appliances supplied by hospital { 2 able to pay, { 2 not able. Cases helped by clergy, W. London Mission, T.C.A.A, &c. 28 Cases referred to clubs and medica! aid societies 428 I have not taken as much advantage of the friendly visiting as I should, partly from knowing that for some time one Committee, from which district quite a fourth of the patients come, was short of workers. The reports I have had have proved most useful and satisfactory : nine became C.O.S. cases, of whom one was procured an in-patient letter for Brompton ; a widow whose husband died in the hospital was made self-supporting ; and a girl was found work in a Cripples' School. The following shows a type of case in which a friendly visitor is so necessary:— G.A.— A child of 6 years was ordered a hip splint, and came with a neighbour, the mother being ill. The visitor saw that if the child had 378/IMSW/A/1/1/9